Joe Celko's analytics and OLAP in SQL - Celko, Joe. (San Francisco, Calif. : Morgan Kaufmann ; Oxford : Elsevier Science [distributor], 2006)
Before SQL programmers could begin working with OLTP (On-Line Transaction Processing) systems, they had to unlearn procedural, record-oriented programming before moving on to SQLs declarative, set-oriented programming. This book covers the next step in your growth. OLAP (On-Line Analytical Processing), Data Warehousing and Analytics involve seeing data in the aggregate and over time, not as single transactions. Once more it is time to unlearn what you were previously taught. This book is not an in-depth look at particular subjects, but an overview of many subjects that will give the working RDBMS programmers a map of the terra incognita they will faceif they want to grow. * Expert advice from a noted SQL authority and award-winning columnist, who has given ten years of service to the ANSI SQL standards committee and many more years of dependable help to readers of online forums. * First book that teaches what SQL programmers need in order to successfully make the transition from transactional systems (OLTP) into the world of data warehouse data and OLAP. * Offers real-world insights and lots of practical examples. * Covers the OLAP extensions in SQL-99; ETL tools, OLAP features supported in DBMSs, other query tools, simple reports, and statistical software.
Basic reports and history -- Cross-tabulations -- Dimension tables -- Data migration and scrubbing -- MERGE statement -- OLAP basics -- GROUPING operators -- OLAP operators in SQL -- Sparseness in cubes -- Data quality -- Correlation -- Data distributions -- Market-basket analysis -- Decision, classification, and regression trees -- Computer-intensive analysis -- Relationship analytics -- Database architectures -- MDX from a SQL viewpoint.
Includes bibliographical references and index.
Keywords: SQL (Computer program language).; OLAP technology; Electronic books